Supreme clientele 2 [compact disc] - Ghostface Killah (Rapper) (Mass Appeal Records, 2025)
A founding member of the legendary Wu-Tang Clan. Ghostface Killah is Hip Hop's masked poet, known for his cinematic storytelling, gritty slang, and razor-sharp delivery. With classic albums like Supreme Clientele and Fishscale, Ghostface carved his name into rap history as one of the most original and consistent voices in the game. The Wait is Over. The Supreme Clientele sequel is here. The highly anticipated album is a vivid late-night noir where every bar brought Ghost's inner thoughts to life.